2020
DOI: 10.1080/13625187.2019.1706079
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol administration prior to intrauterine contraceptive device insertion: a systematic review and meta-analysis of randomised controlled trials

Abstract: INCLUDED STUDIESStudies that fulfilled the requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Also, in a systematic meta-analysis in 2020, Tassi et al concluded that sublingual misoprostol did not show improvement in the facilitation of insertion. However, the use of misoprostol is usually associated with patient comfort 22 . Some other studies did not demonstrate enhancement in the facilitation of insertion 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a systematic meta-analysis in 2020, Tassi et al concluded that sublingual misoprostol did not show improvement in the facilitation of insertion. However, the use of misoprostol is usually associated with patient comfort 22 . Some other studies did not demonstrate enhancement in the facilitation of insertion 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Egger's regression test of funnel plot asymmetry and the rank correlation test by Begg and Mazumdar were used to assess publication bias [13][14][15]. As previously described, heterogeneity between studies was evaluated by I-square index (heterogeneous with a value above 50 %), and the Cochran Q (heterogeneous with a p-value below 0.100) and fixed-or the random-effects model were used as appropriate [16,17]. The primary outcome was presented as a pooled propor-tion with a 95 % confidence interval (CI), where arcsine transformation was used in case of low-prevalence events, and the secondary outcomes were presented as pooled proportion or pooled odds ratio (OR) with 95 % CI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors systematically reviewed all included studies for characteristics that could introduce possible bias (e.g., procedures for participant identification, differences in the duration of follow-ups between cases and controls, the comparability of risk factors for recurrence present at diagnosis for cases and controls). Continuous data were collected as mean and standard deviation according to the previously described methods [ 10 , 11 ]. As previously described, any discrepancies in data extraction or the suitability or otherwise of a study were jointly discussed until a consensus was reached [ 12 ].…”
Section: Methodsmentioning
confidence: 99%